Forecasting Sales Cotton and Polyester Yarn at PT. Agung Sejahtera Sukaraharja Karanganyar - Rukmini Rukmini (Universitas Islam Kadiri, 2019)
This study aims to determine the sales forecasting and polyester cotton yarn in January 2015 by using the Least Square Method and Method of Quadratic Trend. As well as to determine the most efficient methods of forecasting to predict sales of cotton yarn and polyester products at PT Agung Sejahtera. From the results of analysis based on the calculation of sales forecasts yarn products with sales data from January to December 2014 using the least squares method and quadratic trend method, in which the quadratic trend method is more suitable because it has a value of SKP lows while the predictive value of product sales yarn using trend quadratic result of cotton yarn 40 weaving of 1,538 ball, cotton yarn 40 amounted to 597.504 ball spandex, polyster yarn weaving amounted 411.348 40 ball, 30 Weaving Polyester yarn ball at 336.588.